Knowledge Spillover and Emotional Motivation—A Study on the Willingness and Influencing Factors of Project-Based Learning - Ren, Yanyan (Frontiers in Psychology, 2022)
Project-based learning (PBL) is a task-based learning mode, which is of great significance to context-based curriculum education. With data collected through questionnaires and interviews, this article builds a binary logistic regression analysis model to explore the learners' willingness of PBL and its influencing factors. A total of 14 influencing factors are set in the research, with an innovative import of knowledge spillover and emotional motivation, to examine the impact on PBL willingness. Results show that eight factors, such as project-based learning experience, clarity of curriculum tasks, contextuality of curriculum content, and requirement for innovation of curriculum tools, have significant positive impacts on learners' willingness of PBL, while four factors, including the challenge of the curriculum project and tendency of learning objectives setting, have significant negative impacts. What's more, the grade of the learners and the challenge of the curriculum project have no significant impact. This article verifies that individual characteristics, knowledge spillover, and emotional motivation have different directions and degrees of impact on learners' willingness of PBL. Then, reasons are explored and implications proposed that these factors should be distinguished and paid sufficient attention to. Finally, suggestions are put forward on strengthening the contextuality of curriculum content, identifying the heterogeneity of learners, and expanding innovative tools to develop a PBL-based blended teaching model. In this way, the potential of PBL can be fully realized in maximizing learning achievements.